The hemagglutinin envelope protein of canine distemper virus (CDV) confers cell tropism as illustrated by CDV and measles virus complementation analysis. - Stern, L B (1995)
Measles virus (MV) and canine distemper virus (CDV) are morbilliviruses that cause acute illnesses and several persistent central nervous system infections in humans and in dogs, respectively. Characteristically, the cytopathic effect of these viruses is the formation of syncytia in permissive cells. In this study, a vaccinia virus expression system was used to express MV and CDV hemagglutinin (HA) and fusion (F) envelope proteins. We found that cotransfecting F and HA genes of MV or F and HA genes of CDV resulted in extensive syncytium formation in permissive cells while transfecting either F or HA alone did not. Similar experiments with heterologous pairs of proteins, CDV-F with MV-HA or MV-F with CDV-HA, caused significant cell fusion in both cases. These results indicate that in this expression system, cell fusion requires both F and HA; however, the functions of these proteins are interchangeable between the two types of morbilliviruses. Human-mouse somatic hybrids were used to determine the human chromosome conferring susceptibility to either MV and CDV. Of the 12 hybrids screened, none were sensitive to MV. Two of the hybrids containing human chromosome 19 formed syncytia following CDV infection. In addition, these two hybrids underwent cell fusion when cotransfected with CDV-F and CDV-HA (but not MV-F and MV-HA) glycoproteins by using the vaccinia virus expression system. To discover the viral component responsible for cell specificity, complementation experiments coexpressing CDV-HA with MV-F or CDV-F with MV-HA in the CDV-sensitive hybrids were performed. We found that syncytia were formed only in the presence of CDV-HA. These results support the idea that the HA protein is responsible for cell tropism. Furthermore, while the F protein is necessary for the fusion process, it is interchangeable with the F protein from other morbilliviruses.